1993
DOI: 10.1093/ndt/8.6.539
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between donor renal interstitial surface and post-transplant function

Abstract: Forty-three biopsies were performed between 30 and 60 min after reperfusion. Patients (22 males/21 females, mean age 41 +/- 12 years, mean donor age 32 +/- 14 years) were treated either with antilymphocytic globulin, cyclosporin, and prednisolone (24 cases), or OKT3, cyclosporin, and prednisolone (19 cases). Ten patients had delayed post-transplant renal function (DPRF), defined as haemodialysis requirements after surgery, and seven patients had acute rejection 11 +/- 16 days post-transplant. Kidneys were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…Comparable to previous observations, donor age and fibrosis in the pretransplantation biopsy was associated with inferior graft function (29,30). Donor age or quality of the donor organ at implantation was not associated with a higher prevalence of SAR at 6 mo.…”
Section: Discussionsupporting
confidence: 48%
“…Comparable to previous observations, donor age and fibrosis in the pretransplantation biopsy was associated with inferior graft function (29,30). Donor age or quality of the donor organ at implantation was not associated with a higher prevalence of SAR at 6 mo.…”
Section: Discussionsupporting
confidence: 48%
“…Although different morphometric approaches have shown that quantification of chronic renal damage in donor (13)(14)(15) and protocol biopsies (16)(17)(18) correlates with graft outcome, the utility of quantitative parameters as a primary efficacy variable in a hypothetical clinical trial aimed to modify the natural history of CAN has not been explored. Thus, the aim of the present study is to characterize the temporal evolution of intimal thickening and interstitial widening in stable grafts during the first year of follow-up using a morphometric approach.…”
Section: Introductionmentioning
confidence: 99%
“…Nicholson et al ont développé une méthode semiquantitative pour mesurer la fibrose sur des sections biopsiques dont le marquage immunohistochimique reconnaît le collagène III [14]. D'autres ont mesuré le pourcentage de FI sur des sections de biopsies marquées par une solution d'argent-méthénamine par méthode morphomé-trique [15,16]. En effet, le collagène, les fibres de réti-culine ainsi que les muccopolysaccharides de la matrice extracellulaire sont marqués par la méthénamine.…”
Section: Méthodes Morphométriquesunclassified